2008
DOI: 10.1073/pnas.0712309105
|View full text |Cite
|
Sign up to set email alerts
|

Elevated globotriaosylsphingosine is a hallmark of Fabry disease

Abstract: Fabry disease is an X-linked lysosomal storage disease caused by deficiency of ␣-galactosidase A that affects males and shows disease expression in heterozygotes. The characteristic progressive renal insufficiency, cardiac involvement, and neuropathology usually are ascribed to globotriaosylceramide accumulation in the endothelium. However, no direct correlation exists between lipid storage and clinical manifestations, and treatment of patients with recombinant enzymes does not reverse several key signs despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
565
2
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 628 publications
(617 citation statements)
references
References 45 publications
26
565
2
11
Order By: Relevance
“…Finally, although some studies support globotriaosylsphingosine as a potentially useful biomarker for monitoring Fabry disease, this evidence has been generated in relatively recent years. 6,21,22 At the time of the design of the clinical trials included in the current report, globotriaosylsphingosine was not considered a potential surrogate marker of Fabry disease progression or response to treatment and, thus, was not included as a measured end point. The biological reason why changes in plasma or urine Gb 3 concentrations are not useful as biomarkers is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although some studies support globotriaosylsphingosine as a potentially useful biomarker for monitoring Fabry disease, this evidence has been generated in relatively recent years. 6,21,22 At the time of the design of the clinical trials included in the current report, globotriaosylsphingosine was not considered a potential surrogate marker of Fabry disease progression or response to treatment and, thus, was not included as a measured end point. The biological reason why changes in plasma or urine Gb 3 concentrations are not useful as biomarkers is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most male patients with a GVUS demonstrate residual enzyme activity, in contrast to the absent or near absent enzyme activity in classically affected males. Also, previous studies have shown that patients with a nonclassical phenotype often only show a slight increase of lysoGb3 in plasma, while classically affected males invariably have very high levels (Aerts et al 2008;Rombach et al 2010;Gold et al 2013;Lukas et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…This hypothesis is based on increased levels of plasma lyso-Gb 3 , but not Gb 3 , found in most symptomatic female heterozygotes, which appears to be positively correlated with the severity of the clinical picture (Aerts et al 2008). This widely diffusible lyso-Gb 3 might have the capacity to induce cell damage via some mechanism that we do not yet understand well.…”
Section: Discussionmentioning
confidence: 96%